Reputation, price, and death: an empirical analysis of art price formation - Heinrich W. Ursprung; Christian Wiermann (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyze how an artist's death influences the market prices of her works of art. Death has two opposing effects on art prices. By irrevocably restricting the artist's oeuvre, prices, ceteris paribus, increase when the artist dies. On the other hand, an untimely death may well frustrate the collectors' hopes of owning artwork that will, as the artist's career progresses, become generally known and appreciated. By frustrating expected future name recognition, death impacts negatively on art prices. In conjunction, these two channels of influence give rise to a hump-shaped relationship between age at death and death-induced price changes. Using transactions from fine art auctions, we show that the empirically identified death effects indeed conform to our theoretical predictions. We derive our results from hedonic art price regressions, making use of a data set which exceeds the sample size of traditional studies in cultural economics by an order of magnitude.
Keywords: Z11; J24; G12; 330; art price formation; death effect; durable goods monopoly; Kunstgegenstand; Preis; Künstlerische Berufe; Sterblichkeit; Lebensalter; Hedonischer Preis; Theorie; Welt